Design and fabrication of torsion testing machine for reinforced foam concrete - Somkeattikul, Kreetha; Jariyatontivait, Wuttikon; Siripaiboon, Chootrakul (RMUTL Engineering Journal, 2024)
The objective of this research was to design and fabricate a torsion testing machine. Recently, there have been more applications of composite concrete materials for torsion. The torsion testing machine used the principle of torque from the motor with a gear ratio-reduced speed, which was then transmitted to the chain. The load cell was used to measure the force generated by the chain’s tension. During calibration, the standard workpiece properties were compared to the experimental data of the new torsion testing machine, and the results showed that they were acceptable. From the experiments, the torsion resistance values of all three pieces were in the range of 75-100 N·m, and they would break apart after the twisting angle exceeded 35 degrees. In the case of reinforced foam concrete, cracks were observed to appear along the axial direction, confirming torsion. The average torsional resistance of reinforced foam concrete, calculated using formulas that adjusted the densities to approximately 600, 700, and 800 kg/m3, were found to be 13.05, 22.67, and 31.87 N·m, respectively. Furthermore, these findings can be helpful in determining the torsional resistance properties of other materials, such as fiber-concrete and wood-concrete.